2015
DOI: 10.1016/j.actbio.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic intradermal delivery of tumor necrosis factor-alpha antibodies using tip-loaded dissolvable microneedle arrays

Abstract: Tumor necrosis factor-alpha (TNF-α) specific antibodies (anti-TNF-α Ab) have been shown to be potent TNF inhibitors and effective therapeutics for a range of inflammatory diseases. Typically, these drugs are administered systemically, but systemic dosing sufficient to achieve locally effective concentrations in peripheral tissues has been associated with systemic immunosuppression and related adverse events. Here we demonstrate efficient and biologically effective MNA delivery of anti-TNF-α Ab to the intraderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…Therefore, the characterization of cellular responses to soluble cell-signaling molecules and to their gradients is of great importance for understanding how multicellular collective behaviors are organized and regulated. Understanding the roles of gradient sensing in disease also guides us toward novel therapies including regenerative stem cell therapy for neural injury, localized drug delivery for immunomodulation of inflammatory diseases [10] and T-cell engineering for the immunotherapy of cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the characterization of cellular responses to soluble cell-signaling molecules and to their gradients is of great importance for understanding how multicellular collective behaviors are organized and regulated. Understanding the roles of gradient sensing in disease also guides us toward novel therapies including regenerative stem cell therapy for neural injury, localized drug delivery for immunomodulation of inflammatory diseases [10] and T-cell engineering for the immunotherapy of cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Korkmaz et al developed a kind of DMN loaded with anti-TNF-a Ab in the tips of the needles and found that this method demonstrated powerful delivery efficacy and anti-inammation function in BLAB/c mice with psoriatic lesions induced by imiquimod. 52 The MNP, fabricated using low viscosity sodium carboxymethyl cellulose, has a complete appearance and completely dissolved in 30 minutes with the help of an applicator. In a murine psoriasis model, the MNP was observed to have the ability to reduce inammation from the aspects of epidermal thickness, cellular inltrate, and IL-1b mRNA expression.…”
Section: Application Of Microneedles In Psoriasismentioning
confidence: 99%
“…A few weeks ago, two studies showing immunogenicity of a plasmid DNA or adenovirus (serotype 52) expressing virus-like particles in mice and non-human primates were published Abbink et al, 2016). Here, to build on these initial findings to develop an effective ZIKV vaccine, we describe the development of a recombinant adenoviral vector expressing codon-optimized ZIKV E antigen and a subunit recombinant ZIKV E vaccine delivered transcutaneously by carboxymethyl cellulose (CMC) microneedle arrays (MNAs) (Bediz et al, 2014;Korkmaz et al, 2015), investigate their ability to induce neutralizing immune responses, and assess their ability to passively protect against ZIKV challenge in a novel neonatal ZIKV infection mouse model.…”
Section: Introductionmentioning
confidence: 99%